1962
DOI: 10.1093/bja/34.10.721
|View full text |Cite
|
Sign up to set email alerts
|

The Use of D-Tubocurarine in Neonatal Anaesthesia

Abstract: d-Tubocurarine was used in an unselected series of 215 neonates undergoing surgery with only two cases of immediate postoperative respiratory difficulty. The neonate is more sensitive to d-tubocurarine than the adult but this sensitivity decreases during the neonatal period and may be partially explained by changes at the motor end plate and by a diminution in extracellular volume. Overdosage, potentiation by ether and antibiotics, hypothermia and failure to use anticholinesterase drugs are potent causes of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1965
1965
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…These observations led to the notion that newborns may be like myasthenics, and this has been a subject of controversy in the literature ever since. A few years later, an extensive clinical evaluation (Bush & Stead 1962) in neonates found that the initial dose of tubocurarine needed for full control of respiration and adequate clinical relaxation was lowest in the first day of life (0.3 mg. kg-'), increased to 0.44 rng-kg-l by the ninth day and subsequently rose slightly to 0.53 rngakg-'. This observation was confirmed in a later trial involving 50 neonates (Bennett ef aZ.…”
Section: Tubocurarinementioning
confidence: 99%
“…These observations led to the notion that newborns may be like myasthenics, and this has been a subject of controversy in the literature ever since. A few years later, an extensive clinical evaluation (Bush & Stead 1962) in neonates found that the initial dose of tubocurarine needed for full control of respiration and adequate clinical relaxation was lowest in the first day of life (0.3 mg. kg-'), increased to 0.44 rng-kg-l by the ninth day and subsequently rose slightly to 0.53 rngakg-'. This observation was confirmed in a later trial involving 50 neonates (Bennett ef aZ.…”
Section: Tubocurarinementioning
confidence: 99%
“…Reference Ham et al (1978) Stead (1955; Bush and Stead (1962); Lim et al (1964);Churchill-Davidson and Wise (1964) 29 Durrans (1952); Dundee (1954); Chmielewski et al (1978); Gray (1947) McLeod et al (1979 Somogyi (1979) Baraka (1964);Bridenbaugh et al (1966) Miller (1975 Goat et al (1976) Ghoneim et al (1972);Schuh (1977) Katz (1971a,b); Dillon (1969) Fogdall andMiller (1974); Pittinger and Adamson (1972) Miller et al (1976) Miller et al (1972; Stanski et al (1979) Vetten (1973; Dretchen et al (1976) effect may be a separate function of these anticholinesterase agents. However, experiments carried out in greyhound dogs in our laboratory failed to show any change in the plasma concentrations of gallamine when neostigmine and atropine were administered at two dosage levels (unpublished observations).…”
Section: May Enhance Blockmentioning
confidence: 99%
“…When questioned, Dr. Goudsouzian recollected: “One of the issues at that particular time when we started doing anesthesia in kids was ‘are infants more sensitive to muscle relaxants?’ When I looked at the studies I found no convincing studies that infants were not, and they were all observational studies.” Prior studies had been limited by the lack of a precise method to measure muscle relaxation.…”
Section: Twitching Thumbsmentioning
confidence: 99%
“…When I looked at the studies I found no convincing studies that infants were not, and they were all observational studies." Prior studies [13][14][15][16][17][18] had been limited by the lack of a precise method to measure muscle relaxation. Most significant publications included work on the effect of neuromuscular blockers in children, 19,20,[22][23][24] and the use of the laryngeal mask airway in children.…”
Section: General H Ospitalmentioning
confidence: 99%